Local to regional-scale mechanisms behind successful climate services for agriculture in Latin America - Giraldo, Diana; Ríos, David; Navarro-Racines, Carlos; Camacho, Kemly; Martinez-Valle, Armando; Prager, Steven D.; Obando, Diego; Zelaya, Carlos; Martinez-Baron, Deissy; Muñoz, Ángel G.; Ramirez Villegas, Julian (Elsevier, 2025)
The provision of climate services (CS) has grown at an unprecedented rate over the last decade in response to climate-related risks in several sectors of the global economy; this is especially true in agriculture. Several studies document lessons learnt from (un)successful climate services, and attempt to distil these into key principles, recommendations, or requirements. However, limited systematic analysis and data on the characteristics of the CS that are conducive to success exist to date, including for agriculture. Here, we analyse the Local Technical Agroclimatic Committees (referred to here by its Spanish acronym MTAs) as a CS approach that effectively delivers information to farmers sustainably and at local scale. We propose a framework comprising sixteen metrics that help measure the effectiveness, sustainability, and scalability as key dimensions of CS success. We apply this framework to 26 MTAs across four Latin American countries, namely, Guatemala, Honduras, Nicaragua, and Colombia. The analyses revealed that the MTAs played a significant role in CS transformation pathways, producing a total of 158 outcomes (changes in behaviour of people or institutions), and involving at least 279 institutions at various levels and with diverse roles. Analyses of the sixteen metrics revealed a wide range of performance across the 26 MTAs, with nearly half of the MTAs considered to have or nearly-achieved effectiveness, sustainability, and scalability. MTAs success stems not only from an increase in numbers of farmers and locations reached but also from the evolving roles and responsibilities of a diverse ecosystem of actors that accompany enhanced capacities and tangible benefits on the ground. Based on these results, we propose key CS elements, namely, collaboration; participation; adaptability and flexibility; financial (crowd) resourcing; robust governance and strong leadership; awareness of and improvements in data availability, quality, and assurance; capacity development; user-centred communication; adequate incentives; and enabling policy environment.